MINAT MASYARAKAT PETANI TERHADAP PENDIDIKAN AGAMA DI KAMPUNG SIDODADI KECAMATAN SERUWAY KABUPATEN ACEH TAMIANG - Alamsyah Alamsyah (Jurnal Ilmiah Didaktika, 2017)
The focus on this research is to find out why the Sidodadi farmers less interested activity at their mosque.How the Sidodadi farmers participation and contribution in creasing religious education at Sidodadi village; how to involve the problems inreligious activity by the sidoda farmers at mosque.This research is a field research which using qualitative method, the result of in this researchdeals with descriptions form observation and interview with many resetchinformants. There are the farmers, the villager leaders. From the observations, it isfound that the reason why the villagers choose religious activity at home is to increase economy and living standards through social gathering (jula-jula), friendship, to help people who want to send prayers to their parents and relatives who had died.The Participation and contribution of sidodadi farmers in religious activity are the villager leaders motivate their ,people to follow activity and to collect their money to buikl religious place.The problems of sidodadi farmers in religious education at mosque are to avoid social tension because the mosque is located at heighbour village.It is Air Masin village, and then to keep clean the mosque by dirt,such as ur children faecies, refuse of food and drink, cigarette ashes, and the women who are unable to pray and to keep the concentration and absorption prayers of people because this mosque is located on the edge of road that are is much people pas and pray it.